Lightning-generated waves escaping out through plasma holes in the nightside Venus ionosphere - Singh R.N.; Upadhyay H.O. (My University, 2025)
The plasma waves in the Venus ionosphere measured by OEFD aboard PVO are analysed. It is shown that these waves are generated by lightning like cloud-to-cloud discharges anywhere in the Venus ionosphere-surface waveguide. The theoretical minimum attenuation for waveguide mode propagation at 5.4 kHz is consistent with the maximum occurrence rate at this frequency. The lightning-generated and globally-propagating signals when encountered with plasma holes or ion-trough structures escape out partially and are detected by the OEFD aboard PVO. The 100 Hz signals can propagate upwards in whistler mode. Even the localized electrostatic mode waves would be converted into electromagnetic waves in the plasma holes and ion-trough regions. © 1991 Indian Academy of Sciences.